Aminoglycosides in Immunocompromised Critically Ill Patients With Bacterial Pneumonia and Septic Shock: A Post-Hoc Analysis of a Prospective Multicenter Multinational Cohort. Issue 6 (December 2020) - Lopez, René; Rello, Jordi; Taccone, Fabio Silvio; Salem, Omar Ben Hadj; Bauer, Philippe R.; Séguin, Amélie; van de Louw, Andry; Metaxa, Victoria; Klouche, Kada; Martin Loeches, Ignacio; Montini, Luca; Mehta, Sangeeta; et al.
ABSTRACT: Background: The routine use of empiric combination therapy with aminoglycosides during critical illness is associated with uncertain benefit and increased risk of acute kidney injury. This study aimed to assess the benefits of aminoglycosides in immunocompromised patients with suspected bacterial pneumonia and sepsis. Methods: Secondary analysis of a prospective multicenter study. Adult immunocompromised patients with suspected bacterial pneumonia and sepsis or septic shock were included. Primary outcome was hospital mortality. Secondary outcomes were needed for renal replacement therapy (RRT). Mortality was also assessed in neutropenic patients and in those with confirmed bacterial pneumonia. Results were further analyzed in a cohort matched on risk of receiving aminoglycosides combination. Results: Five hundred thirty-five patients were included in this analysis, of whom 187 (35%) received aminoglycosides in addition to another antibiotic effective against gram-negative bacteria. Overall hospital mortality was 59.6% (58.3% vs. 60.3% in patients receiving and not receiving combination therapy; P  = 0.71). Lack of association between mortality and aminoglycosides was confirmed after adjustment for confounders and center effect (adjusted OR 1.14 [0.69–1.89]) and in a propensity matched cohort (adjusted OR = 0.89 [0.49–1.61]). No association was found between aminoglycosides and need for RRT (adjusted OR = 0.83 [0.49–1.39], P  = 0.477), nor between aminoglycoside use and outcome in neutropenic patients or in patients with confirmed bacterial pneumonia (adjusted OR 0.66 [0.23–1.85] and 1.25 [0.61–2.57], respectively). Conclusion: Aminoglycoside combination therapy was not associated with hospital mortality or need for renal replacement therapy in immunocompromised patients with pulmonary sepsis. Abstract : Supplemental Digital Content is available in the text